Marketing Section Performance Improvement Companies Post Covid-19 in Indonesia - Andriani, Devi; Pristiyono, Pristiyono; Hanum, Fauziah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This paper was conducted to find solutions to problems regarding incentives and compensation for the performance of the company's marketing department, because in general the human resources in the company, especially the marketing department, must-have skills because in finding consumers, skills are needed so that consumers are interested in the goods offered. Based on the results of the study, it is known that there is no significant effect between compensation on morale, this can be seen from the results of the path coefficient value of 0.200 and the p-value of 0.276 > 0.50. Therefore, it can be stated that this hypothesis testing is rejected. Based on the results of the study, it is known that there is a significant influence between incentives on work morale, this can be seen from the results of the path coefficient value of 0.261 and the p-value of 0.013 < 0.50. Therefore, it can be stated that this hypothesis testing is accepted. Based on the results of the study, it is known that there is a significant influence between incentives on performance, this can be seen from the results of the path coefficient value of 0.244 and the p-value of 0.000 < 0.50. Therefore, it can be stated that this hypothesis testing is accepted. Based on the results of the study, it is known that there is a significant influence between compensation on performance, this can be seen from the results of the path coefficient value of 0.197 and the p-value of 0.045 < 0.50. Therefore, it can be stated that this hypothesis testing is accepted. Based on the results of the study, it is known that there is a significant influence between work morale on performance, this can be seen from the results of the path coefficient value of 0.129 and the p-value of 0.020 < 0.50. Therefore, it can be stated that this hypothesis testing is accepted.